ANALISIS KANDUNGAN Β-KAROTEN PADA BEBERAPA VARIETAS CABAI MERAH (CAPSICUM ANNUUM) SECARA SPEKTROFOTOMETRI UV-VIS - Harti Widiastuti (As-Syifaa Jurnal Farmasi, 2011)
A have applied of research about content of β-carotene in three quality of cabai namely cabai merah besar (Capsicum annuum L. Var. Abreviata Einger huth), cabai merah keriting (Capsicum annuum L. Var. Longum sendt) and cabai rawit (Capsicum frustescens L). For to Analysis and senelles content β-carotene in cabai.                Cabai sample to be extraction in demarcation by acetone. The result of extraction to extract again with petroleum eter and applied safonification with KOH 15%. Qualitative analysis applied with Chromatography method in thin layer using petroleum eter : Benzen (9:1).The result it showing there are spot which same on three samples and β-carotene pure as the compere. While Quantitative analysis with spectrofotometri visible using β-carotene pure as compere showing that the content of β-carotene cabai merah besar 154,32 mg/g, cabai merah keriting 181,41 mg/g and cabai rawit 146,85 mg/g.A have applied of research about content of β-carotene in three quality of cabai namely cabai merah besar (Capsicum annuum L. Var. Abreviata Einger huth), cabai merah keriting (Capsicum annuum L. Var. Longum sendt) and cabai rawit (Capsicum frustescens L). For to Analysis and senelles content β-carotene in cabai.                Cabai sample to be extraction in demarcation by acetone. The result of extraction to extract again with petroleum eter and applied safonification with KOH 15%. Qualitative analysis applied with Chromatography method in thin layer using petroleum eter : Benzen (9:1).The result it showing there are spot which same on three samples and β-carotene pure as the compere. While Quantitative analysis with spectrofotometri visible using β-carotene pure as compere showing that the content of β-carotene cabai merah besar 154,32 mg/g, cabai merah keriting 181,41 mg/g and cabai rawit 146,85 mg/g.